Genome-wide screens reveal shared and strain-specific genes that facilitate enteric colonization by Klebsiella pneumoniae - Bettina H. Cheung; Arghavan Alisoltani; Travis J. Kochan; Marine Lebrun-Corbin; Sophia H. Nozick; Christopher M. R. Axline; Kelly E. R. Bachta; Egon A. Ozer; Alan R. Hauser (mBio, 2023)
ABSTRACTGastrointestinal (GI) colonization by Klebsiella pneumoniae is a risk factor for subsequent infection as well as transmission to other patients. Additionally, colonization is achieved by many strain types that exhibit high diversity in genetic content. Thus, we aimed to study strain-specific requirements for K. pneumoniae GI colonization by applying transposon insertion sequencing to three classical clinical strains: a carbapenem-resistant strain, an extended-spectrum beta-lactamase-producing strain, and a non-epidemic antibiotic-susceptible strain. The transposon insertion libraries were screened in a murine model of GI colonization. At 3 days post-inoculation, 27 genes were required by all three strains for colonization. Isogenic deletion mutants for three genes/operons (acrA, carAB, and tatABCD) confirmed colonization defects in each of the three strains. Additionally, deletion of acrA reduced bile tolerance in vitro, while complementation restored both bile tolerance in vitro and colonization ability in vivo. Transposon insertion sequencing suggested that some genes were more important for the colonization of one strain than the others. For example, deletion of the sucrose porin-encoding gene scrY resulted in a colonization defect in the carbapenemase-producing strain but not in the extended-spectrum beta-lactamase producer or the antibiotic-susceptible strain. These findings demonstrate that classical K. pneumoniae strains use both shared and strain-specific strategies to colonize the mouse GI tract.IMPORTANCEKlebsiella pneumoniae is a common cause of difficult-to-treat infections due to its propensity to express resistance to many antibiotics. For example, carbapenem-resistant K. pneumoniae has been named an urgent threat by the United States Centers for Disease Control and Prevention. Gastrointestinal colonization in patients with K. pneumoniae has been linked to subsequent infection, making it a key process to control in the prevention of multidrug-resistant infections. However, the bacterial factors which contribute to K. pneumoniae colonization are not well understood. Additionally, individual strains exhibit large amounts of genetic diversity, begging the question of whether some colonization factors are strain dependent. This study identifies the enteric colonization factors of three classical strains using transposon mutant screens to define a core colonization program for K. pneumoniae as well as detecting strain-to-strain differences in colonization strategies.